2017
DOI: 10.2307/j.ctt1wc7rdn
|View full text |Cite
|
Sign up to set email alerts
|

Social Media in Emergent Brazil

Abstract: They were active collaborators with whom I openly discussed my ideas about, and understanding of, technology, family, social life, prejudices, personal history and affection. Unfortunately I cannot mention any of their names here to protect their privacy. My wife and I owe an enormous debt of gratitude to Professor Daniel Miller, my mentor and supervisor on this project. He has offered generous amounts of feedback, support and patience with my shortcomings and delays. Above all, he has been an exemplar of a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 16 publications
1
17
0
5
Order By: Relevance
“…But it has also acted as a 'weaponized' chat app for the dissemination of misinformation during the 2018 Brazilian Presidential elections (Pereira and Bojczuk, 2018; see also Nemer, 2018;Córdova and Barbosa, 2019). Despite these potentially contradictory manifestations, it is increasingly popular among ordinary users in Brazil (Spyer, 2017) as well as politically-active individuals. Little research however has focused on Whatsapp as such.…”
Section: The Blast Of Whatsapp and Its Siblingsmentioning
confidence: 99%
“…But it has also acted as a 'weaponized' chat app for the dissemination of misinformation during the 2018 Brazilian Presidential elections (Pereira and Bojczuk, 2018; see also Nemer, 2018;Córdova and Barbosa, 2019). Despite these potentially contradictory manifestations, it is increasingly popular among ordinary users in Brazil (Spyer, 2017) as well as politically-active individuals. Little research however has focused on Whatsapp as such.…”
Section: The Blast Of Whatsapp and Its Siblingsmentioning
confidence: 99%
“…A esmagadora participação feminina no projeto dá comprovação de que, em uma sociedade como a nossa, de origens escravocratas e afinada ao patriarcado ocidental, o cuidado de crianças recai maciça e iniquamente sobre as mulheres, principalmente às mais empobrecidas e, entre estas, às mulheres negras (Bazzo, 2020c). Por seu turno, o fato de a maior parte das membras residir nas regiões Sul e Sudeste, as duas mais ricas do país, evidencia disparidades socioeconômicas na geografia, as quais se espelham em índices de inclusão digital, considerados nesse domínio tanto o acesso pleno às tecnologias da informação e comunicação, quanto o necessário letramento para delas usufruir (Spyer, 2017).…”
Section: Procedimentos Metodológicos E Resultadosunclassified
“…On the other hand, most qualitative studies have concluded that individuals often prefer using platforms for everyday matters than for political expression (Boczkowski et al, 2018a; Harlow, 2017; Haynes, 2016; Nemer, 2016). Based on ethnographic research in a small Brazilian town, Spyer (2017) concluded that “party politics is the very last thing that people in Balduíno discuss on social media” (p. 189). It is possible that the focus on Twitter and Facebook, to the detriment of other platforms such as Instagram, Snapchat, and WhatsApp, has contributed to further overestimating the role of political issues within social media.…”
Section: Actorsmentioning
confidence: 99%
“…Some studies have centered on how social media enable information dissemination and political expression (Halpern et al, 2017; Serrano-Puche et al, 2018; Spyer, 2017). Custódio (2017) reported on how “Mare Vive,” the Facebook page of the favelas of Complexo da Mare in Rio de Janeiro, Brazil, “denounces political violence, governmental neglect” and celebrates “local culture and traditions” (p. 103).…”
Section: Effectsmentioning
confidence: 99%